AI in enhancing zakat’s role in collection and distribution: A model for digital transformation in Islamic philanthropy - Wahab, Abdul; Mahdiya, Ilma; Afdhali, Muhammad Hasan (Review of Islamic Social Finance and Entrepreneurship, 2026)
Purpose – This study aims to develop a conceptual model for integrating artificial intelligence (AI) into zakat management to enhance the effectiveness of zakat collection and distribution while ensuring sustainability, transparency, and alignment with Sharia principles in the context of digital transformation of Islamic philanthropy.Methodology – This study adopts a qualitative conceptual approach based on a systematic literature review and theory building. The analytical framework integrates the technology organization environment (TOE), institutional theory, and maqasid al-Sharia approaches to map the relationships among key constructs influencing AI adoption and governance in zakat institutions.Findings – This study proposes a conceptual model of AI-enabled zakat management, indicating that technological readiness, organizational capabilities, environmental pressures, and institutional legitimacy are critical determinants of successful AI adoption in zakat governance. The findings also highlight that maqasid al-Sharia functions as an ethical anchor, guiding AI utilization toward distributive justice, wealth protection, and social welfare, rather than purely technical efficiency.Implications – Theoretically, this study expands the literature on digital zakat and values-based digital transformation by positioning AI as an institutional and ethical instrument. Conceptually, this model provides an analytical framework for zakat institutions, regulators, and Sharia technology developers to design legitimate, inclusive, and sustainable digital zakat governance.Originality – This study offers an original contribution by integrating the TOE framework, institutional theory, and maqasid al-Sharia into a single conceptual model, positioning AI not as a neutral technology but as a socio-technical system that must align with the normative objectives of zakat and Islamic ethics.